Artistic image as the factor of activaaaan of creative potential of the person (Pedagogy of Higher and Secondary Education, 2006)
The article deals with the problem of en image as a semiotic unit of visual communication and its factor activate creative potential and delopment of spiritual make-up students arce done.
Keywords: image; sign; symbol; creative potential